Massive Iatrogenic Outbreak of Human Immunodeficiency Virus Type 1 in Rural Cambodia, 2014–2015. (4th December 2017) - Rouet, François; Nouhin, Janin; Zheng, Du-Ping; Roche, Benjamin; Black, Allison; Prak, Sophearot; Leoz, Marie; Gaudy-Graffin, Catherine; Ferradini, Laurent; Mom, Chandara; Mam, Sovatha; Gautier, Charlotte; et al.
Abstract : This study provided the serologic, genomic, and geospatial investigation of an iatrogenic outbreak that was recognized in rural Cambodia in 2014–2015, showing a massive and spatially localized outbreak of HIV, associated with HCV infections, but a lack of HBV diffusion. Abstract: Background: In 2014–2015, 242 individuals aged 2–89 years were newly diagnosed with human immunodeficiency virus type 1 (HIV-1) in Roka, a rural commune in Cambodia. A case-control study attributed the outbreak to unsafe injections. We aimed to reconstruct the likely transmission history of the outbreak. Methods: We assessed in 209 (86.4%) HIV-infected cases the presence of hepatitis C virus (HCV) and hepatitis B virus (HBV). We identified recent infections using antibody (Ab) avidity testing for HIV and HCV. We performed amplification, sequencing, and evolutionary phylogenetic analyses of viral strains. Geographical coordinates and parenteral exposure through medical services provided by an unlicensed healthcare practitioner were obtained from 193 cases and 1499 controls during interviews. Results: Cases were coinfected with HCV (78.5%) and HBV (12.9%). We identified 79 (37.8%) recent (<130 days) HIV infections. Phylogeny of 202 HIV env C2V3 sequences showed a 198-sample CRF01_AE strains cluster, with time to most recent common ancestor (tMRCA) in September 2013 (95% highest posterior density, August 2012–July 2014), and a peak of 15 infections/day in September 2014. Three geospatial HIV hotspots were discernible in Roka and correlated with high exposure to the practitioner ( P = .04). Fifty-nine of 153 (38.6%) tested cases showed recent (<180 days) HCV infections. Ninety HCV NS5B sequences formed 3 main clades, 1 containing 34 subtypes 1b with tMRCA in 2012, and 2 with 51 subtypes 6e and tMRCAs in 2002–2003. Conclusions: Unsafe injections in Cambodia most likely led to an explosive iatrogenic spreading of HIV, associated with a long-standing and more genetically diverse HCV propagation.